How Organizational Support Strengthens the Impact of Individual Adaptability on Work Satisfaction and Employee Performance - Yovita Insan Perwita Utami; Sunaryo, Sinto (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of service quality and customer experience on digital transaction security through customer trust as a mediating variable at Bank BRI Surakarta. Data were collected from 165 active BRImo users using a Likert-scale questionnaire and analyzed with SmartPLS. The results show that customer trust significantly affects transaction security. Service quality and customer experience also significantly influence customer trust and indirectly affect transaction security through customer trust. These findings confirm that customer trust plays a central role in strengthening the security of digital transactions. Keywords: Employee Performance; Individual  Adaptability; Job Satisfaction; Perceived Organizational Support (POS)